A CULTURE “FULL OF CHOICE APOPHTHEGMS AND USEFUL MAXIMS”: INVENTED PROVERBS IN C.S. LEWIS’ THE HORSE AND HIS BOY - Unseth, Peter (Proverbium - Yearbook, 2011)
The use of created proverbs in fiction by C.S. Lewis’ friend J.R.R. Tolkein has been described in detail, but this is the first examination of the creation of proverbs by Lewis. Lewis created several proverbs in his novel The Horse and His Boy, part of six-volume work, The Chronicles of Narnia. All of these proverbs are found in just three conversations. This paper identifies and examines the proverbs, showing how Lewis used them to help portray the imaginary culture of the Calormen, a culture proudly described as “full of choice apophthegms and useful maxims”. Additionally, Lewis subtly had his characters use proverbs in ways that revealed aspects of the various speakers’ character. The use of proverb creation by other authors of fiction is also discussed.